2022
DOI: 10.3389/fimmu.2021.785941
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Recovered From the Plasma of COVID-19 Patients Expose SARS-CoV-2 Spike-Derived Fragments and Contribute to the Adaptive Immune Response

Abstract: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by beta-coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that has rapidly spread across the globe starting from February 2020. It is well established that during viral infection, extracellular vesicles become delivery/presenting vectors of viral material. However, studies regarding extracellular vesicle function in COVID-19 pathology are still scanty. Here, we performed a comparative study on exosomes recovered from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 66 publications
2
76
0
Order By: Relevance
“…During viral infections, extracellular vesicles of 30-100 nm are normally produced from a broad array of cells and, in certain cases, can present viral antigens to the host immune system. A study evaluating exosomes isolated from plasma of COVID-19 patients has shown that exosomes of mild patients (which were of B cell, DC, and monocyte/macrophages origin) contained a higher number of SARS-CoV-2 antigens and were able to induce CD4 T cell activation compared to exosomes isolated from severe COVID-19 patients, suggesting that exosomes can contribute to prime adaptive immune responses, thus reducing the severity of disease (198).…”
Section: Exosomesmentioning
confidence: 99%
“…During viral infections, extracellular vesicles of 30-100 nm are normally produced from a broad array of cells and, in certain cases, can present viral antigens to the host immune system. A study evaluating exosomes isolated from plasma of COVID-19 patients has shown that exosomes of mild patients (which were of B cell, DC, and monocyte/macrophages origin) contained a higher number of SARS-CoV-2 antigens and were able to induce CD4 T cell activation compared to exosomes isolated from severe COVID-19 patients, suggesting that exosomes can contribute to prime adaptive immune responses, thus reducing the severity of disease (198).…”
Section: Exosomesmentioning
confidence: 99%
“…Another laboratory has detected S1 (RBD) on the surface of intact plasma exosomes of COVID‐19 patients, that were anchored to a surface by anti‐exosome antibodies. 41 As for the mitochondrial proteins, it is not possible yet to assume that NDEV levels of SARS‐CoV‐2 proteins accurately reflect those in the central nervous system. Nonetheless, the mean levels of both S1 and N were significantly higher in ADEVs and NDEVs of all affected subgroups than background levels in controls.…”
Section: Discussionmentioning
confidence: 99%
“…This will require longitudinal studies of a larger number of patients at multiple times from acute COVID‐19 into PASC with many different manifestations and through complete resolution without and with treatments. With much larger numbers of plasmas to study, it may be necessary to introduce a faster and more efficient hybrid technology between our techniques and those of Pesce, et al 41 This would involve anchoring all plasma EVs to wells by an anti‐EV surface antibody and then double labeling with a neuron‐specific antibody and an analyte‐directed antibody. Some additional mitochondrial analytes should be included in these analyses for parallel assessment of inflammation with neural cell dysfunction and identification of potential drug targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transfer of certain viral components such as S protein can act as a natural vaccine and stimulate the production of neutralizing antibody titers 46,47 . It has been shown that viral protein materials such as S protein can be packed and transferred by Exo in patients with mild and severe COVID‐19 47 . These features can lead to proper activity of antigen‐presenting cells and T lymphocyte function 47 .…”
Section: Engineered Exo For the Inhibition Of Viral Infectionsmentioning
confidence: 99%